2018
DOI: 10.1097/md.0000000000011625
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of transcutaneous vagus nerve stimulation for poststroke epilepsy

Abstract: Background:This study assessed the effect transcutaneous vagus nerve stimulation (TVNS) for poststroke epilepsy (PSE).Methods:Fifty-two patients with PSE were included in this study. Twenty-seven patients received TVNS, 30 minutes each session, once daily, twice weekly for a total of 4 weeks; and were assigned to the treatment group. Twenty-five patients were at waiting list and were assigned to the control group. The primary outcome included weekly seizure frequency. The secondary outcomes consisted of each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The effectiveness of invasive cervical VNS in patients with drug-resistant epilepsy has been demonstrated repeatedly (Pakdaman et al, 2016;Kawai et al, 2017;Vivas et al, 2017). Furthermore, some initial trials on noninvasive transcutaneous auricular VNS reported promising results (He et al, 2013;Bauer et al, 2016;Barbella et al, 2018), although not all studies demonstrated effectiveness (Song et al, 2018). Other potential clinical indications for VNS, such as heart failure (Premchand et al, 2014;Zannad et al, 2015;Gold et al, 2016), Crohn's disease (Bonaz et al, 2016), chronic pain management (Chakravarthy et al, 2015), and obesity (Bodenlos et al, 2007;Pardo et al, 2007;Bodenlos et al, 2014) are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of invasive cervical VNS in patients with drug-resistant epilepsy has been demonstrated repeatedly (Pakdaman et al, 2016;Kawai et al, 2017;Vivas et al, 2017). Furthermore, some initial trials on noninvasive transcutaneous auricular VNS reported promising results (He et al, 2013;Bauer et al, 2016;Barbella et al, 2018), although not all studies demonstrated effectiveness (Song et al, 2018). Other potential clinical indications for VNS, such as heart failure (Premchand et al, 2014;Zannad et al, 2015;Gold et al, 2016), Crohn's disease (Bonaz et al, 2016), chronic pain management (Chakravarthy et al, 2015), and obesity (Bodenlos et al, 2007;Pardo et al, 2007;Bodenlos et al, 2014) are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Vier prospektive Studien, die eine bilaterale tVNS mit 20 Hz an wendeten, berichteten über eine signifikante Reduktion der An fallshäufigkeit: He et al [41] [45]. Zwei weitere Studien fanden keinen signifikanten Effekt bei post Stroke-Epilepsie [46] und bei allgemein pharmakorefraktärer Epilepsie [47]. Insgesamt ist damit die Evidenz für die Wirksamkeit von tVNS bei der Reduzierung der Anfallshäufigkeit eingeschränkt, es fehlen vergleichende Studien mit Einsatz unterschiedlicher Geräte und unilateraler vs. bilatera ler Stimulation.…”
Section: Transcutane Vagusnervstimulationunclassified
“…None of the mild AEs required changes in therapy protocol and all of them self-resolved during the follow-up period (34,47,49). Four studies reported AEs in transcutaneous VNS, observing fatigue, dizziness, ear pain, skin redness and tiredness (43,45,53). In the study by Capone et al (transcutaneous VNS) there were no adverse events and patients did not report discomfort from the procedure (46).…”
Section: Safetymentioning
confidence: 99%